2005
DOI: 10.1111/j.0022-1112.2005.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clay particles on the cutaneous exchange of oxygen across the chorion of Atlantic salmon eggs

Abstract: Rates of oxygen consumption for Atlantic salmon Salmo salar embryos approaching hatching were determined. Values were recorded using a 'closed system' experimental set-up. A magnetic stirrer was used to ensure that zones of oxygen depletion did not develop in the microenvironment surrounding the respiring eggs. Recorded values of oxygen consumption ranged from 0Á0024 to 0Á0038 mg O 2 egg À1 h À1 , with a mean consumption rate of 0Á0032 mg O 2 egg À1 h À1 . The values of oxygen consumption were similar to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 19 publications
2
49
1
1
Order By: Relevance
“…However, many ways in which fine sediment impacts upon fish egg survival, are not represented in SIDO-UK; e.g. the surface sealing caused by sand (Beschta and Jackson, 1979), the impacts of clay biofilms around eggs (Greig et al, 2005) and sediment-associated contaminants. The findings from this study, and the further application of SIDO-UK, may have significant implications for informing the management of sediment delivery to salmonid rivers (Collins and McGonigle, 2008;Collins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many ways in which fine sediment impacts upon fish egg survival, are not represented in SIDO-UK; e.g. the surface sealing caused by sand (Beschta and Jackson, 1979), the impacts of clay biofilms around eggs (Greig et al, 2005) and sediment-associated contaminants. The findings from this study, and the further application of SIDO-UK, may have significant implications for informing the management of sediment delivery to salmonid rivers (Collins and McGonigle, 2008;Collins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Chapman, 1988;Sear et al, 2008) have found that sediment infiltration into the redd reduces the spawning success rate. There have been several hypotheses put forward to explain this observation: (a) physical blockage of intragravel pores, where the reduction in gravel porosity and permeability results in the reduction in intragravel flow velocities and therefore a decrease in the supply of oxygen rich water to the egg zone; (b) sediment oxygen consumption, where the organic matter associated with the finer size classes decomposes using oxygen, meaning it becomes limiting for egg survival, and; (c) egg membrane micropores are blocked (Greig et al, 2005) limiting metabolic exchanges. The success of salmonid spawning is therefore a function of the coincidence of fine sediment delivery and the development of the salmonid eggs during the incubation period.…”
Section: Introductionmentioning
confidence: 99%
“…Colmation describes the process leading to clogging of river beds with fine sediments due to gravitational settling, advection and further infiltration deep into the bed matrix (Boano et al, 2014;Lawler et al, 2009). This limits oxygen supply to salmonid eggs and restricts the hyporheic flow that is crucial for processing contaminants and flushing out waste products (Greig et al, 2005(Greig et al, , 2007Sear et al, 2014). It also limits the emergence of recently hatched fry by creating a seal (Sear et al, 2008).…”
Section: Fine Sediment Impacts and Ecological Implicationsmentioning
confidence: 99%
“…Coarser fractions of the suspended sediment load are more likely to be deposited, increasing the erodibility of macrophyte beds ( Jones et al, 2012a) and clogging redds (Greig et al, 2005), whereas finer particles (< 2 µm) are more likely to affect the respiratory organs and feeding apparatus of fish and invertebrates (Bilotta and Brazier, 2008). Clay-sized (<4 µm) particles can be trapped by periphyton, reducing its attractiveness to grazing organisms (Graham, 1990).…”
Section: Fine Sediment Impacts and Ecological Implicationsmentioning
confidence: 99%
“…Le taux d'incorporation des fractions < 1 mm est faible (augmentation de 12 % par rapport à leurs valeurs initiales), et la proportion d'éléments > 5 mm demeure sensiblement la même. Toutefois, des proportions de sables et de fines < 2mm telles que celles observées (18 % ou plus) sont suffisantes pour réduire la disponibilité d'oxygène pour les oeufs (GREIG et al, 2005) et induire des mortalités conséquentes. Ainsi, des proportions de 15 à 20 % de ces éléments entraînent de fortes baisses de survie chez diverses espèces de salmonidés dans les frayères (MCNEIL, 1964 ;TAGART, 1976 ;HAUSLE et COBLE, 1976) ou en milieu contrôlé (PETERSON et METCALFE, 1981 ;LAPOINTE et al, 2004).…”
Section: Caractéristiques Granulométriquesunclassified